FROM DISCOUNTS TO DECISIONS: THE ROLE OF BRAND REPUTATION IN TIKTOK GO'S F&B CONSUMER ECOSYSTEM - Novia Fitri Yanti Saragih; Herning Indriastuti; Heni Rahayu Rahmawati (CV. Radja Publika, 2026)
This study aims to examine the effect of TikTok discount vouchers on consumer purchase decisions in the food and beverage (F&B) sector, with brand reputation as a mediating variable within the social commerce ecosystem. The growing use of TikTok Go as a promotional channel reflects a shift in consumer behavior from passive content exposure to transaction-driven digital engagement. However, the effectiveness of discount strategies in this context is not solely determined by price incentives, but also by perceived brand reputation. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a survey of consumers who have used TikTok discount vouchers for F&B products. The results indicate that TikTok discount vouchers have a positive and significant effect on both brand reputation and purchase decisions. Furthermore, brand reputation significantly influences purchase decisions and acts as a mediating variable in the relationship between discount vouchers and purchase decisions. These findings suggest that the effectiveness of discount strategies in social commerce depends not only on price-based stimuli but also on the ability of brands to maintain a strong reputation. This study contributes to digital marketing literature by highlighting the integration of price promotions and brand perception in shaping consumer behavior.